Membangun Daya Saing Dengan Visualisasi Motif pada Dinding Perahu Fiber Buatan Galangan Desa Lengkong - Rochyat, Indra Gunara; FauzI, Muhammad; Yusuf, Adisti Ananda (Institut Seni Indonesia Surakarta, 2023)
Lengkong village shipyard in Cilacap was formed to answer the demands of traditional fishermen in Cilacap. Accommodative means of transportation create a sense of pleasure and a sense of love for him. Love is shown on the walls of the hull unit which is a space for fishermen's artistic expression in symbolizing the design of a motif that means speed. The problem of the lack of variations in shapes or motifs produced by fishermen and boat craftsmen shows the monotony of the resulting designs. The lack of variety of designs is suspected of a decline in boat sales at the shipyard. For this reason, insight is needed in the form of counseling to improve the creativity of craftsmen. This shipyard requires various adaptations, especially in direct view to attract the attention of fishermen. This visualization is of course obtained from the meaning of denotation on the wall of the hull unit in the form of a symbol that means speed so that fishermen are more interested in taking boats from this shipyard. The target of the PKM program is a productive fishing community. The purpose of the counseling program is to improve the creative thinking skills needed by craftsmen to encourage the emergence of various designs that are applied to the walls of the hull unit which have an impact on the diversity of motifs and patterns. The visual appeal will certainly increase the shipyard's competitiveness against other shipyards. Through an active psychomotor method with a fast, precise, and correct design pattern, it produces a stimulant in the form of stimulation of the power of imagination. The results of this counseling are expected to be able to help increase the creativity of fishermen and craftsmen under the auspices of shipyards.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//